2022
DOI: 10.1016/j.jbc.2021.101495
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Gq/11 signaling acutely drives and chronically sustains metabolic reprogramming in uveal melanoma

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Our data further highlights that targeting this process in UM may enhance treatment efficacy and indicates the potential use of CysLT 1 antagonists to inhibit OXPHOS in a combinatorial treatment approach with alternative immune or traditional targeted therapies. UM does not exhibit a classical Warburg effect ( 84 ). Onken et al ( 84 ) report that that oncogenic G q/11 signaling in UM cell lines promotes both glycolytic activity and mitochondrial respiration ( 84 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data further highlights that targeting this process in UM may enhance treatment efficacy and indicates the potential use of CysLT 1 antagonists to inhibit OXPHOS in a combinatorial treatment approach with alternative immune or traditional targeted therapies. UM does not exhibit a classical Warburg effect ( 84 ). Onken et al ( 84 ) report that that oncogenic G q/11 signaling in UM cell lines promotes both glycolytic activity and mitochondrial respiration ( 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…UM does not exhibit a classical Warburg effect ( 84 ). Onken et al ( 84 ) report that that oncogenic G q/11 signaling in UM cell lines promotes both glycolytic activity and mitochondrial respiration ( 84 ). Additionally, metabolic heterogeneity in BAP1 mutant vs. BAP1 wild-type UM was recently described based on oxidative phosphorylation gene expression profiles ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…The potential and reported connections of Gαq signaling that we have described with this axis [ 21 ] may provide new insights in the mechanisms underlying these metabolic alterations. Recent studies have further confirmed the relevance of Gαq signaling for driving metabolic reprogramming in uveal melanoma [ 211 ] and in the regulation of glucose and lipid homeostasis [ 212 ] reinforcing a critical role of GPCR-Gαq system in metabolic diseases. Further investigation will be required to define the mechanisms involved.…”
Section: Autophagy In Disease For Good and For Bad: Gαq Involvementmentioning
confidence: 96%
“…Inhibition of mitogenic Gα q/11 signaling by application of FR to models expressing Gα q Q209L/P mutants has been demonstrated in several instances. Treatment with FR resulted in reduced tumor growth in mouse xenografts, , reduced glucose uptake in uveal melanoma cells in vitro and in vivo, and decreased colony formation of uveal melanoma cells in 3D cell culture . As these effects cannot be attributed to the GDI properties of FR, inhibitor binding was hypothesized to switch the nucleotide preference of Gα q Q209L/P from GTP to GDP in an allosteric fashion .…”
Section: Molecular Mechanism Of Gαq Protein Inhibition By Ym and Frmentioning
confidence: 99%